Near-infrared light-triggered theranostics for tumor-specific enhanced multimodal imaging and photothermal therapy - Wu B (Dove Medical Press, 2017)
Bo Wu,1,* Bing Wan,2,* Shu-Ting Lu,1 Kai Deng,3 Xiao-Qi Li,1 Bao-Lin Wu,1 Yu-Shuang Li,1 Ru-Fang Liao,1 Shi-Wen Huang,3 Hai-Bo Xu1,2 1Department of Radiology, Zhongnan Hospital of Wuhan University, 2Department of Radiology, Union Hospital of Tongji Medical College, Huazhong University of Science and Technology, 3Department of Chemistry, Key Laboratory of Biomedical Polymers, Ministry of Education, Wuhan University, Wuhan, People’s Republic of China *These authors contributed equally to this work Abstract: The major challenge in current clinic contrast agents (CAs) and chemotherapy is the poor tumor selectivity and response. Based on the self-quench property of IR820 at high concentrations, and different contrast effect ability of Gd-DOTA between inner and outer of liposome, we developed “bomb-like” light-triggered CAs (LTCAs) for enhanced CT/MRI/FI multimodal imaging, which can improve the signal-to-noise ratio of tumor tissue specifically. IR820, Iohexol and Gd-chelates were firstly encapsulated into the thermal-sensitive nanocarrier with a high concentration. This will result in protection and fluorescence quenching. Then, the release of CAs was triggered by near-infrared (NIR) light laser irradiation, which will lead to fluorescence and MRI activation and enable imaging of inflammation. In vitro and in vivo experiments demonstrated that LTCAs with 808 nm laser irradiation have shorter T1 relaxation time in MRI and stronger intensity in FI compared to those without irradiation. Additionally, due to the high photothermal conversion efficiency of IR820, the injection of LTCAs was demonstrated to completely inhibit C6 tumor growth in nude mice up to 17 days after NIR laser irradiation. The results indicate that the LTCAs can serve as a promising platform for NIR-activated multimodal imaging and photothermal therapy. Keywords: light triggered, near-infrared light, tumor-specific, multimodal imaging, photothermal therapy, contrast agents